(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The Al-Qur’an contains many stories and history from ancient people so that it can be used as a lesson for its readers. In the Qur’an, there is a sura whose name is Surah Yusuf. This Surah Yusuf revolves around the story of the Prophet Yusuf and his brothers and their parents. Where it tells about the envy of Yusuf’s brothers, Yusuf was sold to al-Aziz Egypt so that he was adopted as a child, the temptation of a woman which resulted in him being imprisoned, then appointed as a royal official, then reunited with his family. The Prophet Yusuf is one of the Prophets who has advantages both from his handsome face, his morals and interpreting the veil of dreams. There are many commendable (mahmudah) and reprehensible (madzmumah) moral values ​​in the story of the prophet Yusuf which can be used as a basic foundation in increasing faith, although there are various kinds of trials it faces. This study aims to find out how the life journey of the Prophet Yusuf and what moral values ​​are contained in his story in the Qur’an sura Yusuf. This research uses a type of library research or qualitative research analysis. Sources of research data were obtained from a number of books, opinions, Qur’anic arguments and others. The data collection technique in this study is a procedure. Sources of research data were obtained from a number of books, opinions, Qur’anic arguments and others. The data collection technique in this study is a procedure. Sources of research data were obtained from a number of books, opinions, Qur’anic arguments and others. The data collection technique in this study is a procedure.